Performance optimization for UAV-enabled V2I communications system - Fang GUO; Yu-yan ZHANG; Long ZHAO; Kan ZHENG; Wen-bo WANG (物联网学报)
In the emergency communication,UAVs (unmanned aerial vehicle) are used more and more widely,and a V2I (vehicle to infrastructure) vehicle communication technology based on UAV was proposed.Because of the communication distance and the shelter of the terrain,the ground vehicle and the base station may not connect directly.At this time,the UAV can be used as communication relay.In the process of communication,in order to meet the fairness of ground vehicle communication,a time interval less than the coherence time was selected based on the coordinates of moving ground vehicles,the transmission rate between vehicles in each time interval are calculated to maximize the minimum transmission rate as the optimization goal.In order to solve this problem,the entire communication process was dispersed.First,UAV flight trajectory to maximize the minimum transmission rate at each time interval within the range of the UAV flight path was calculated to get the whole communication process trajectory.Simulation results show that through the path planning of UAV,the information transmission rate of the vehicle is obviously better than the transmission rate under the fixed position of UAV.